Phytochemical Profiling of a Common Moss Hyophila involuta Jaeger. for its Bioactive and Antioxidant Potential Against Viral Infections - Sing, Swati; Sharma, Rimjhim; Joshi, Supriya; Nagaraju, Ganji Purnachandra; Vats, Sharad; Alam, Afroz (The Scientific Temper, 2022)
Among terrestrial plants, bryophytes constitute a major part of biodiversity and designated as the second largest taxonomic group after angiosperms. It is estimated about 20,000 to 25,000 species of mosses, liverworts and hornworts are existing worldwide. Like angiosperms they also have many ecological and economic impending, especially medicinal value. However, due to natural attraction and practical ease usually angiosperms have been a preferred choice as reservoirs of medicinally important phytoconstituents, and this group of plants has been neglected for a long time despite having many important biologically active compounds. Mosses, the largest taxonomical group of bryophytes, traditionally known for their therapeutic values and their extracts have found various applications in ethnopharmacology. Many of the species of mosses have shown high biological activities and, in several studies, it has been confirmed that mosses have remarkable antibacterial, antiviral and antifungal activities. There have not been any valid reports of viruses infecting bryophytes, and thus it seems possible that bryophytes contain a chemical defense against viruses including COVID-19 due to the presence of secondary metabolites, viz., terpenoids, flavonoids and bis-bibenzyls, etc., and some of the bryophytes species have been identified as exhibiting considerable antiviral activity. But, due to their small size, difficulty in collection and identification majority of mosses is remain unexplored for the therapeutic purposes, especially in India. Hence, this preliminary attempt has been made to screen a commonly growing moss species Hyophila involuta Jaeger. for its phytochemical profile and bioactive potential.